Experimental study and proposed power correlation for laminar burning velocity of hydrogen-diluted methane with respect to pressure and temperature variation. (29th January 2022) - Eckart, Sven; Pizzuti, Loreto; Fritsche, Chris; Krause, Hartmut
Abstract: The aim of the present work is to contribute to the better understanding of the combustion process and the laminar flame properties of methane/hydrogen-air flames at elevated temperatures and pressures. The heat flux method provides an accurate and direct measurement of laminar burning velocities (LBV) at elevated temperatures, while the constant volume chamber method provides measurements at elevated pressures. In the present work, a database of more than 250 experimental points for the range of temperature (298–373 K) and pressure conditions (1–5 bar) for mixtures up to 50% hydrogen in methane was generated using these two methods. Comparison with the sparse literature data shows quite good agreement. A power-law correlation for temperature and pressure is proposed for methane/hydrogen-air mixtures, which has a practical application in estimating the LBV of a natural gas/hydrogen mixture intended to replace pure natural gas in different processes. The power-law temperature exponent, α, and the pressure exponent, β, show inverse trends. The former decreases almost linearly and the latter increases approximately linearly when the hydrogen content is increased. The power-law exponents are highly affected by the mixture equivalence ratio, ϕ, showing a parabola like trend. However, for the pressure exponent this trend becomes almost linear for 50% H2 in the mixture. The power-law correlation has been validated against experimental data for a wide range of temperature (up to 573 K), pressure (1–7.5 bar), equivalence ratios ( ϕ between 0.7 and 1.3) and H2 contents up to 50%. Graphical abstract: Image 1 Highlights: Heat flux method and constant volume chamber were used to investigate the LBV. 50% H2 in CH4 were investigated at ϕ = 0.6–1.6, pgas = 1–5 bar and Tgas = 298–373 K. Combined power law correlation for T and p of CH4 /H2 /air mixtures was proposed. Correlation validated against the dataset with the highest T and the highest p. Correlation validated against literature up to 50% H2, up to 7.5 bar and up to 573 K.